Kesalahan Ejaan dan Tanda Baca Pada Berita Online Terbitan Karanganyarnews - Natalia Puspita Kusuma Sari; Afrida Kusuma Wardani; Sri Muryati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article discusses the importance of language as a communication tool and its role in conveying information effectively. The main focus of the research is the analysis of spelling and punctuation errors in online news published by Karanganyarnews from 24 October to 15 November 2024. The research method used is descriptive qualitative, which aims to describe and analyze the language errors found. The results showed 21 errors, consisting of 15 spelling errors and 6 punctuation errors. These errors include the use of standard words, capital letters, and the use of foreign languages. These findings emphasize that correct understanding and application of language rules is very crucial to avoid misunderstandings in communication. In conclusion, errors in writing can interfere with readers’ understanding, so writers are expected to pay more attention to language rules in writing.